Adequacy of Fixed-Dose Heparin Infusions for Venous Thromboembolism Prevention after Microsurgical Procedures - Bertolaccini, Corinne M.; Prazak, Ann Marie B.; Agarwal, Jayant; Goodwin, Isak A.; Rockwell, W. Bradford; Pannucci, Christopher J. (Journal of Reconstructive Microsurgery, 2018)
Background In microvascular surgery, patients often receive unfractionated heparin infusions to minimize risk for microvascular thrombosis. Patients who receive intravenous (IV) heparin are believed to have adequate prophylaxis against venous thromboembolism (VTE). Whether a fixed dose of IV heparin provides detectable levels of anticoagulation, or whether the “one size fits all” approach provides adequate prophylaxis against VTE remains unknown. This study examined the pharmacodynamics of fixed-dose heparin infusions and the effects of real-time, anti-factor Xa (aFXa) level driven heparin dose adjustments.Methods This prospective clinical trial recruited adult microvascular surgery patients placed on a fixed-dose (500 units/h) unfractionated heparin infusion during their initial microsurgical procedure. Steady-state aFXa levels, a marker of unfractionated heparin efficacy and safety, were monitored. Patients with out-of-range aFXa levels received protocol-driven real-time dose adjustments. Outcomes of interest included aFXa levels in response to heparin 500 units/h, number of dose adjustments required to achieve goal aFXa levels, time to reach goal aFXa level, and 90-day clinically relevant bleeding and VTE.Results Twenty patients were recruited prospectively. None of 20 patients had any detectable level of anticoagulation in response to heparin infusions at 500 units/h. The median number of dose adjustments required to reach goal level was five, and median weight-based dose to reach goal level was 11.8 units/kg/h. Real-time dose adjustments significantly increased the proportion of patients with in-range levels (60 vs. 0%, p = 0.0001). The 90-day VTE rate was 5% and 90-day clinically relevant bleeding rate was 5%.Conclusions Fixed-dose heparin infusions at a rate of 500 units/h do not provide a detectable level of anticoagulation after microsurgical procedures and are insufficient for the majority of patients who require VTE prophylaxis. Weight-based heparin infusions at 10 to 12 units/kg/h deserve future study in patients undergoing microsurgical procedures to increase the proportion of patients receiving adequate VTE prophylaxis.
Keywords: heparin; plastic surgery; microvascular surgery; venous thromboembolism; anti-factor Xa